PENGENALAN PENGELOLAAN KEUANGAN GEN Z : JAJAN CERDAS DAN CATATAN BERKELAS - Kesha Nur Agnia; Agnia Nabila Septiani; Gea Khairunisa; Irene Alya Poputra; Intan Rahma Sari (Publika Citra Media, 2026)
Generation Z is now in the spotlight in various aspects, especially regarding lifestyle and how they manage their finances. Living and growing up in the digital era makes Gen Z highly influenced by technology that simplifies various aspects of life, including how they spend their money. However, many young people still experience difficulties in managing their allowance due to a lack of understanding about priorities and financial planning. This Community Service activity was carried out as a form of social concern for this issue by providing financial literacy education to students at SMP Cita Mulia. The material provided included the difference between needs and wants, as well as how to do simple financial recording. The delivery was conducted using a participatory, learning-by-playing method through a combination of material explanation, question-and-answer sessions, and educational games so that the learning felt more enjoyable. This activity has been proven to increase students’ learning interest and strengthen their understanding of basic concepts of daily financial management and record-keeping. Through this activity, it is expected that students can build wiser and more directed financial habits from an early age.